Needs Analysis of Medical Personnel’s English Communication Skills - Ratmo Ratmo; Tutut Sumartini (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
Globalization brings new challenges for education and training program as it demands new skills, awareness, approaches, and training. This demands medical personnel to serve clients who come from other countries around the world with effective English communication skill. In a more specific purpose in a job setting, an employee will need specific English related to his job description. As far as medical profession is concerned, medical personnel need English language in their professional settings. The demand for English for Occupational Purposes (EOP) grows proportionally to the universal demand for employees, who can function in English, in their fields of specialization. It therefore demands medical personnel to acquire English competences to meet with their desired level of English proficiency skills. What English competences are needed and whether they need English training program will determine the urgency needs analysis on the medical personnel English communication skills. This study is aimed at investigating the communicative needs of medical personnel at professional level in survey-based research. The data were collected, analyzed and interpreted qualitatively by administering observational notes, interview, and questionnaire among medical representatives. Further, this study is expected to gain beneficial outputs such as research report, proceeding after having been presented in national or international conference, and could be further developed into learning module for training program.